The Leadership Role in The Smart-Village Program in Banyuwangi District, East Java - Ella Lesmanawaty' Wargadinata (Institut Pemerintahan Dalam Negeri, 2021)
The use of information communication technology (ICT) in government administration has changed the face of Weber's conventional bureaucracy into a modern model. The electronic or digital-based government model is an important milestone in this 21st century due to its ability to improve government performance, thereby increasing public satisfaction. The successful implementation of e-government is influenced by many beneficial and nonbeneficial determining factors, such as leadership. Therefore, this research aims to explore the leadership role of the Smart village program implemented in 2010 by the Banyuwangi District Government using a qualitative approach. Data were collected through observation in selected locations, interviews, and secondary sources. The data obtained were processed using the NVivo application process due to its ability to capture and build inductively concepts that describe research based on local perspectives. The results processed through the word cloud feature illustrate two interesting analyses. First Smart village is considered an online administration service by the Banyuwangi people because it is easy, fast, open, and full of certainty. Second leadership has 5 important roles, namely Charismatic, Innovative, Consistent, Cooperation, and Integrity. In conclusion, the success of e-government is strongly influenced by the usefulness of services for the community and the seriousness of the leadership to implement e-government not only as a political gimmick but to serve the community. Keywords: Digital service, Transformational Leadership, Digital Society, Openness